Dengue virus replication in infected human keratinocytes leads to activation of antiviral innate immune responses - Pornapat Surasombatpattana (2018)
Dengue virus (DENV) infection is the most prevalent mosquito-borne viral diseases in the world. Vector-mediated transmission of DENV is initiated when a blood-feeding female Aedes mosquito injects saliva, together with the virus, into the skin of its mammalian host. Understanding the role of skin immune cells in the activation of innate immunity to DENV at the early times of infection is a critical issue that remains to be investigated. The purpose of our study was to assess the contribution of human keratinocytes as potential host cells to DENV in the activation of immune responses at the anatomical site of mosquito bite. We show that primary keratinocytes support DENV replication with the production of negative-stranded viral RNAs inside the infected cells. In the course of DENV life cycle, we observed the activation of host genes involved in the antiviral immune responses such as intracellular RNA virus sensors Toll-Like Receptor-3, Retinoic Acid Inducible Gene-I, Melanoma Differentiation Associated gene-5 and the RNA-dependent protein kinase R. DENV infection of primary keratinocytes also resulted in up-regulation of the expression of the antiviral Ribonuclease L gene, which subsequently led to enhanced production of IFN-β and IFN-γ. Depending on stages of viral replication, we observed the activation of host genes encoding the antimicrobial proteins β-defensin and RNase 7 in infected keratinocytes. Our data demonstrate for the first time the permissiveness of human epidermal keratinocytes to DENV infection. Remarkably, DENV replication in keratinocytes contributes to the establishment of antiviral innate immunity that might occur in the early times after the bite of mosquito. © 2011.